2019
DOI: 10.5812/msnj.88742
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Spiritual Coping and Spiritual Wellbeing in Patients with Beta-Thalassemia Major

Abstract: Background: Thalassemia is one of the most prevalent genetic disorders with numerous physical and psychological side effects. Spiritual wellbeing and spiritual coping are important resources for dealing with the complications of chronic diseases. Objectives: The present study aimed at investigating the relationship between spiritual coping and spiritual wellbeing in patients with beta-thalassemia major in Zahedan in 2016.Methods: This descriptive-correlational study was conducted on 150 β-thalassemia major pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have shown that those who benefit from spiritual coping are more adapted to the complications and stresses of illness (36, 37). The role of spirituality in hope and coping with illness and overcoming anxiety and worry has been shown in various studies 10 , 19 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that those who benefit from spiritual coping are more adapted to the complications and stresses of illness (36, 37). The role of spirituality in hope and coping with illness and overcoming anxiety and worry has been shown in various studies 10 , 19 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the search result using the Google Scholar database, twelve article were found that were considered to be in accordance with the research that was raised, namely about the influenced factors of spiritual well-being. The twelve article will be described in Table 1 1, it can be seen that spiritual well-being is influenced by several factors, including: mental health (Hamka et al, 2019), spiritual coping (Sadeghi et al, 2018), life satisfaction Mathad et al, al., 2019;Alorani & Alradaydeh, 2018;Baykay, 2022), hope (Yangoobzadeh et al, 2018, primary emotions (Hebler-Ragger, 2018), mindfulness (Mathad et al, 2019), selfcompassion (Mathad et al, 2019), perceived social support (Alorani & Alradaydeh, 2018), quality of life (Ayik et al, 2019), adjustment to diseases (Ayik et al, 2019),…”
Section: Resultsmentioning
confidence: 99%